Does Perceived Harm Underlie Effects of Vehicle Size on Overtaking Judgments during Driving?. (September 2018) - Levulis, Samuel J.; DeLucia, Patricia R.; Yang, James; Nelson, Vivian
Previous research found that participants accepted more gaps during overtaking (in a driving simulator) when the oncoming vehicle was a motorcycle compared with larger vehicles (Levulis, DeLucia & Jupe, 2015). Results were due to the size of the vehicle independently of the type of the vehicle, and represented shifts in response bias instead of sensitivity. The implication is that drivers may perceive motorcycles as being farther away or travelling more slowly than larger vehicles due to their relatively small sizes, contributing to crashes that result from right-of-way violations (Hurt, Ouellet, & Thom, 1981; Pai, 2011). However, in Levulis et al. (2015) vehicle size was correlated with the perceived threat of collision and associated harm posed by the oncoming vehicle (collision with larger vehicles is more harmful than with smaller vehicles). To eliminate this confound, a driving simulator was used to examine whether overtaking judgments are influenced by the size of an oncoming vehicle even when threat of (simulated) collision is removed. The size-arrival effect occurred nevertheless, suggesting that participants relied on perceived distance and speed rather than perceived harm. Countermeasures to misjudgments of gaps during overtaking should include driver-assistance technologies and driver education.